The students of Right-bank Ukrainian pedagogical universities in 1920-1930ʼs: the archival funds’ analysis - Komarnitsky, Oleksandr (Pedagogical Discourse, 2013)
A number of the Central State Archives of the higher authorities, public organizations of Ukraine funds, public archives of Vinnytsia, Zhytomyr, Kyiv, Cherkasy, Khmelnytsky region, the city of Kyiv, which contain multifaceted information on the student history of teacher training institutions in the Right-bank Ukraine 20-30-s of the XX century are analyzed in this article. Displaying potential information of archival sources, which are well represented higher education normative-legal acts of Bolshevik government, student stuff formation documents, educational and socio- political activities of young people, their financial situation and everyday life.